Training healthcare assistants working in adult acute inpatient wards in Psychological First Aid: An implementation and evaluation study. Issue 6 (16th April 2020) - Kantaris, Xenya; Radcliffe, Michelle; Acott, Kevin; Hughes, Peter; Chambers, Mary
Abstract: What is known on the subject: Healthcare assistants are untrained and unregistered frontline staff but are expected to be proactive in preventing and responding to 'untoward' incidents quickly and efficiently when working within adult acute inpatient psychiatric settings. Healthcare assistants should be trained to provide enhanced care to service users residing in acute psychiatric settings. To date, a training programme in Psychological First Aid has not been expended in such a setting with nonregistered staff. What the paper adds to existing knowledge: The study demonstrates that training healthcare assistants in Psychological First Aid is useful in improving their confidence in caring for service users, therapeutic engagement with service users and ward culture in general. What are the implications for practice: A training programme in Psychological First Aid for healthcare assistants to enhance ward culture can be implemented in different practice environments. Psychological First Aid is harmonious with nursing values and provides healthcare assistants with a relevant, useful and easily understood toolkit to apply in acute psychiatric settings. Abstract: Introduction: Healthcare assistants working within adult acute inpatient psychiatric settings are untrained and unregistered, however, they can contribute to quality service if they receive some training. Psychological First Aid training has never been expended in these settings, so this study intends to fill this gap in the existing evidence with this category of healthcare personnel. Aim: The aim of this study was to introduce and evaluate first aid training for healthcare assistants. Method: A pre/post design was adopted to gather data using questionnaires and interviews. The groups of participants included 16 healthcare assistants trained in Psychological First Aid, a sample of service users and four ward managers. Results: Post‐training, (a) healthcare assistants and service users ranked the therapeutic milieu of the ward more favourably, (b) the self‐efficacy of the healthcare assistants increased, and the number of 'untoward' incidents decreased, and (c) health care assistants' confidence in their skills was high. The ward manager interviews post‐training revealed four themes: (a) staff utilization of new skills and renewed enthusiasm, (b) calmer atmosphere on the ward and staff togetherness, (c) confidence and reflection on practice and (d) therapeutic engagement. Discussion: Training healthcare assistants is useful in improving staff confidence, therapeutic engagement with service users and ward culture in general. Implications for practice: Techniques and skills learnt are relevant and useful to healthcare assistants and provide an easily understood toolkit that is harmonious with nursing values. If executed correctly, the training can enhance practice and care outcomes and the overall service user experience.